Communicative musicality. Exploring the basis of human companionship. - Malloch, Stephen; Trevarthen, Colwyn (New York Oxford university press, 2009)
Communicative Musicality explores the intrinsic musical nature of human interaction. The theory of communicative musicality was developed from groundbreaking studies showing how in mother/infant communication there exist noticeable patterns of timing, pulse, voice timbre, and gesture. Without intending to, the exchange between a mother and her infant follow many of the rules of musical performance, including rhythm and timing. This is the first book to be devoted to this topic. In a collection of cutting-edge chapters, encompassing brain science, human evolution, psychology, acoustics and music performance, it focuses on the rhythm and sympathy of musical expression in human communication from infancy. It demonstrates how speaking and moving in rhythmic musical ways is the essential foundation for all forms of communication, even the most refined and technically elaborated, just as it is for parenting, good teaching, creative work in the arts, and therapy to help handicapped or emotionally distressed persons. A landmark in the literature, Communicative Musicality is a valuable text for all those in the fields of developmental, educational, and music psychology, as well as those in the field of music therapy.